Advancing Parkinson’s disease biopathology and drug discovery by dual cellular modelling - Chua, Pin Fen; Nurr Maria Ulfa, Seruji; Mas Atikah, Lizazman; Vivien Jong, Yi Mian; William K., Lim (Elsevier B.V., 2024)
Parkinson’s disease (PD) is the fastest growing neurological disorder in the world. Its pathologic hallmarks are dopaminergic neuronal loss in the substantia nigra and alpha-synuclein accumulation in neurons. However, the patho-biologic mechanisms are largely unknown. Current drugs cannot slow or halt disease progression while clinical trials are mostly unsuccessful. Hence better cellular models are needed for pathological and drug dis covery studies prior to in vivo validation. PC12 cells are commonly used for neurotoxicity studies but the Neuroscreen-1 (NS-1) variant has a faster doubling time and higher basal rate of neurite growth. We developed a NS-1 PD model with the neurotoxin 6-hydroxydopamine (6-OHDA) and MTT cell viability assay as readout. We optimized 6-OHDA concentration to a uniquely low 10 µM for a closer approximation to in vivo neurotoxicity. NS1 cells treated with 6-OHDA displayed hallmark dopamine loss and apoptotic cell death. We used the model to screen a series of xanthones − polyphenolic compounds found in many medicinal plants. We report a novel activity of thwaitesixanthone in the PD model. The model was validated using alpha-mangostin (a neuro protectant in in vivo and in vitro PD models) which was the most active in restoring cell viability. Alpha-synuclein is now a therapeutic target for stopping PD progression. Human HEK293 cells have neuronal attributes and reported to express pathologic alpha-synuclein. We hypothesized the transfection-efficient HEK293T cells is an optimal cell line for monitoring human alpha-synuclein levels. We make the first report that 6-OHDA treatment increased pathologic alpha-synuclein expression in HEK293T cells. This alpha-synucleinopathy model was validated using alpha-mangostin which attenuated 6-OHDA-induced pathologic alpha-synuclein to baseline levels. Thus we developed a novel NS-1 PD model more representative of in vivo neurotoxicity complemented by a human HEK293T cell-based alpha-synucleinopathy model for tracking pathologic alpha-synuclein levels. We present these dual models for producing in vitro findings with increased likelihood of clinical translation.